(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2018)
The aim of this article is to reflect on the role played by the subject Social History within the curriculum of the Nursing Degree in two aspects: on the one hand, the institutionalization of the profession as such and, on the other hand, the process of feminization of the profession in Argentina throughout the 20th century. For this, we will revisit one of the didactic forms used in class, such as the analysis of documentary films. Given that they carry an interpretation on the expansion of the health system, the consolidation of public bodies, the training of professional nurses and the influence of some nursing references in particular and of Argentine medicine in general, allow us to analyze the discursive construction of these processes, as well as some social stereotypes around the profession.